2007
DOI: 10.21608/mjfmct.2007.48851
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Protective Effect of Natural Honey Against Cadmium-Induced Hepatotoxicity and Nephrotoxicity

Abstract: The therapeutic properties of natural honey once considered a form of folk or preventive medicine. It is important for the treatment of acute and chronic free radical mediated diseases and toxicity. Oxidative stress can play a key role in cadmium-induced dysfunction. The aim of this work was to study the effect of natural honey on cadmium-induced liver and kidney damage. A total of 30 adult male rats were divided into three groups. Group I animals served as control were injected daily I.P. by 1 ml saline. Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 44 publications
6
17
0
Order By: Relevance
“…The drastic pathological changes in tissues of the studied organs (kidney, liver, testis, and stomach) of the tartrazine‐treated group is consistent with Mehedi et al () and Al‐Seeni et al (). Restoring the studied tissues their normal histology with honey treatment may be due to its content of ascorbic acid, flavonoids, catalase, phenolic compounds, and tocopherols (Abdel‐Moneim & Ghafeer, ; Al‐Seeni et al, ; Hassan, ; Sarkar & Ghosh, ).…”
Section: Discussionmentioning
confidence: 99%
“…The drastic pathological changes in tissues of the studied organs (kidney, liver, testis, and stomach) of the tartrazine‐treated group is consistent with Mehedi et al () and Al‐Seeni et al (). Restoring the studied tissues their normal histology with honey treatment may be due to its content of ascorbic acid, flavonoids, catalase, phenolic compounds, and tocopherols (Abdel‐Moneim & Ghafeer, ; Al‐Seeni et al, ; Hassan, ; Sarkar & Ghosh, ).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the first experimental evidence for the hepatoprotective effect of natural honey under exposure to Cd derive from the investigation by Abdel‐Moneim and Ghafeer (). In this study, animals were co‐administered with 0.05 mL natural honey dissolved in water i.g.…”
Section: Polyphenol‐rich Products In Protection and Treatment Of Cd‐imentioning
confidence: 99%
“…The consumption of honey also decreased the intensity of lipid peroxidation in the plasma and liver to the control values. Furthermore, the structural changes in the hepatocytes caused by exposure to this metal (Table ) were returned to nearly normal as a result of the impact of honey (Abdel‐Moneim & Ghafeer, ). The research by Abdelaziz et al () has demonstrated that p.o.…”
Section: Polyphenol‐rich Products In Protection and Treatment Of Cd‐imentioning
confidence: 99%
See 2 more Smart Citations